HUBUNGAN ANTARA BODY IMAGE DAN PERILAKU MAKAN DENGAN STATUS GIZI REMAJA PUTRI DI SMA THERESIANA SEMARANG - Widianti, Nur; Kusumastuti, Aryu Candra (Journal of Nutrition College, 2012)
Background: The dissatisfaction with their body shapes is commonly found among female adolescents. The lack of the contentment lead them to gain an ideal body shape but, unfortunately, they implement improper eating behaviour. The extreme diet they have affects negatively to their nutritional status. This study was aimed at analyzing the association between the body image and eating behaviour with nutritional status of female adolescents. Methods: The study was cross-sectional on 72 female students of grade X, XI and XII in Theresiana Senior High School Semarang. The samples were taken based on simple random sampling. The samples were fulfilled inclusive criterion. The data were gathered by using questionnaires and focus group discussion (FGD). The FGD was intended to find more data on body image. Nutritional status data was obtained by measuring weight and height.Â  Then, z-score was calculated based on BMI/ U by using WHO Anthro Plus 2007. Results: A total of 29 subjects (40.3%) were not satisfied with their body shape and 43 subjects (59.7%) were satisfied with their body shape. The majority (56.9%) subjects have not good eating behavior yet, whereas 43.1 % of them have good eating behavior. There were significant association between body image with nutritional status (r = 0.482 p = 0.001) and eating behavior with nutritional status (r = 0.507 p = 0.001). Conclusion: Body image and the eating behavior were associated with nutritional status of female adolescents.